Approaches to Interrogating the Human Memory B-Cell and Memory-Derived Antibody Repertoire Following Dengue Virus Infection - Lyski, Zoe L.; Messer, William B. (Frontiers in Immunology, 2019)
Memory B-cells (MBCs) are potential antibody secreting immune cells that differentiate and mature following host exposure to a pathogen. Following differentiation, MBCs remain in peripheral circulation after recovery and are poised to secrete antigen-specific antibodies if and when they are re-exposed to their cognate antigen. Consequently, MBCs form the founder population and provide one of the first lines of pathogen-specific defense against reinfection. The role MBCs play is complicated for viruses that are heterologous, such as dengue virus (DENV), which exist as antigenically different serotypes. On second infection with a different serotype, MBCs from initial dengue infection rapidly proliferate and secrete antibodies: many of these MBC derived antibodies will be cross-reactive and weakly neutralizing, while some antibodies may recognize epitopes conserved across serotypes and have the capacity to broadly neutralize 2 or more serotypes. It is also possible that a new population of MBCs and antibodies specific for the second virus serotype need to arise for long-term broader immunity to develop. Methods to interrogate and track memory B cell responses are important for evaluating both natural immunity and vaccine response. However, the low abundance of MBCs for any specific pathogen makes it challenging to interrogate frequency, specificity, and breadth for the pathogen of interest. This review discusses current approaches that have been used to interrogate the memory B cell immune response against viral pathogens in general and DENV specifically. Including strengths, limitations, and future directions. Single-cell approaches could help uncover the DENV specific MBC antibody repertoire, and improved methods for isolating DENV specific monoclonal antibodies from human peripheral blood cells would allow for a functional analysis of the anti-DENV repertoire.